Vitamin D Status of Adults in the Outpatient Department in Bangladesh (Journal of Dhaka Medical College, 2018)
Background: Vitamin D deficiency (VDD) is widespread, yet it is the most underdiagnosed and undertreated nutritional deficiency in the world. The prevalence of VDD is estimated to affect over 1 billion people worldwide. The present study was conducted to estimate the prevalence of VDD among adults aged 18–89 years visiting the outpatient department in a clinic/chamber.Objective: To assess the status of vitamin D deficiency (VDD) among the adult population in Bangladesh.Methods: A cross sectional study was conducted among 189 adults in the year 2017 including both males and females aged 18–89 years in outpatient department of a clinic/chamber. Venous blood sample was collected for the measurement of Vitamin D (25 hydroxyvitamin D).Results: This study included a total of 189 adults (29 males and 160 females) aged between 18 and 89 years. Majority of the patients were vitamin D deficient, 67.2% and 20.6% were suffering from vitamin D insufficiency. Maximum males and females are deficient, 69% and 66.9% respectively where as a very small percentage has sufficient level of vitamin D.Conclusions: Vitamin D deficiency (VDD) is alarmingly high. Screening services should be implemented while researchers focus on strategies to lessen the incidence and morbidity associated with these conditions.J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 94-97